Analisis Efektivitas Protokol Autentikasi Jaringan Nirkabel Berdasarkan Parameter (QoS) - Ummi Rufaidah Hamka; Nurul Syafirah; Muh. Aprian Naufal; Asipa Febriana; Nurpadila Nurpadila; Nurjannah Nurjannah; Ketrin Rinayanti Manullang (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The need for wireless networks (Wi-Fi) in academic environments such as the University of West Sulawesi continues to increase along with the increasing number of users. However, the surge of connected devices without access control burdens the Access Point, resulting in a decrease in service quality such as unstable connections and high data delivery failures. This study aims to analyze the effectiveness of implementing a wireless network authentication protocol based on Quality of Service (QoS) parameters using the Telecommunications and Internet Protocol Harmonization Over Network (TIPHON) standard. The method used is Action Research by monitoring and processing Wi-Fi network traffic data using Wireshark software in two different locations, namely Building A (without an authentication system) and the Library (with an authentication system). The QoS parameters tested include throughput, packet loss, delay, and jitter. The results show that both locations have an average QoS index of 2.25 (Moderate Category). Building A boasts superior throughput of 466 Kbps, but its delay (157.1 ms) and jitter (42.06 ms) performance are less stable, with packet loss reaching 85.17% due to the density of freely connected external devices. In contrast, the Library, which implemented an authentication system, had significantly superior network stability, with a highly responsive delay of 9.54 ms (Excellent) and jitter of 4.51 ms (Good), despite its lower throughput capacity of 144 Kbps. This study concludes that implementing an authentication system is a fundamental requirement for limiting the number of unauthorized users, preventing traffic congestion, and maintaining stable network service quality on campus.